Eredità di Antonio Banfi nel pensiero di Raffaele De Grada sulla storia e critica d’arte: dagli anni della formazione all’attività della Fondazione Corrente (Materiali di Estetica. Terza serie, 2022)
The article analyzes Raffaele De Grada’s thinking about art history and criticism, underlying the influence of Antonio Banfi’s teaching from his education to Fondazione Corrente’s debates in the 80’ies. By studying unpublished and little-known archival sources, it emerges how De Grada’s writings were focused on a thought opened to different points of view, such as historical context and artwork’s tecnique, to avoid an idealistic aesthetic. Moreover, De Grada conceived both art history and criticism as a political action, inspired by the ethical value of the person and of the creative human vision against any aestheticism or alienation
Keywords: Raffaele De Grada; Art History and Criticism; Corrente; Antonio Banfi; Philosophy; Scuola di Milano